Uji Toksisitas Akut ekstrak Etanol Bunga Turi Putih (Sesbania grandiflora (L.) Pers.) Terhadap Parameter SGOT dan SGPT pada Organ Hati Tikus Putih Jantan (Rattus norvegicus) Galur Wistar - Fikih Putri Ayu Nabila; Jamilatur Rohmah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Turi plants contain phenolic compounds, tannins, flavonoids, alkaloids, and glycosides. In addition, Turi plants also contain potentially toxic compounds such as pyrrolizidine compounds. This study aimed to determine the acute toxicity of ethanol extract of white turi flowers on toxic symptoms, macroscopic observation of liver organs, and measurement of SGOT and SGPT levels. This type of research is a laboratory experimental study using the Post Test Only Control Group Design research design. Rats were divided into four groups: standard control, 10,000, 15,000, and 20,000 mg/kgBB, then observed for toxic symptoms, liver macroscopic, and SGOT-SGPT levels. Phytochemical test results showed that turi flowers contain alkaloid, saponin, tannin, steroid, and triterpenoid compounds. Macroscopic observation of the liver showed normal condition. The results of the One-way ANOVA test on SGOT and SGPT levels showed significant differences in each group. Based on the results of the study, it can be concluded that there is toxicity of ethanol extract of white turi flower to rats seen from toxic symptoms that appear but have not caused death in rats. Besides that, white turi flower extract can affect increasing SGPT and SGPT levels